Strategi Amerika Serikat dalam Menghadang Pengembangan Senjata Nuklir Korea Utara dengan Memanfaatkan Posisi Strategis Guam Sebagai Wilayah Unincorporated Territory - Rahardian, Baharian Aristya; Utomo, Tri Cahyo (Journal of International Relations, 2020)
As a sovereign nation, The United States of America is certainly very concerned about national security and aware of the threats that come. One of the main threats of the United States is the North Korean nuclear weapons development program or so-called ICBM which began to be intensively developed since 2016. The presence of this threat certainly creates a sense of worry that makes America strengthen its defense and security, one of only by maximizing the existence of Guam as the Unincorporated Territory. This thesis is structured to find out the United States' ef orts in utilizing the strategic position of Guam as an unincorporated territory to North Korea's aggressiveness and compiled using Descriptive Analytical methods using the theory of Defensive Realism and Security Dilemmas as a rationale. This thesis argues that the ef orts of the United States in overcoming the aggressiveness of the development of North Korea's nuclear weapons through the utilization of the strategic position of Guam as an Unincorporated Territory are somewhat successful. Because if viewed from the scale of pure military power, Guam is far more superior to North Korea and the threat of a nuclear weapons attack that North Korea aimed at the United States will are viewed only as a bluf s